A Study of the Impact of Digital Visual Merchandising on Customer Purchasing Behavior in Tiktok Live Sessions - Gunadi, Heru (PT FORMOSA CENDEKIA GLOBAL, 2024)
The purpose of this paper is to report the findings of a study carried out by Indonesia lighting brand Rexx to determine how digital visual banners, a component of visual merchandising, affect consumer interaction behaviour during Tiktok live sessions. Visual merchandising aims to draw in, hold the attention of, and inspire consumers to watch, join sessions and interact. In this study, the visual merchandising elements studied were limited to visual banners which also included creative displays, designs and layouts. Moving forward, it is planned to include more elements. The methodology used in this study is a descriptive quantitative methodology, with the unit of analysis being the 4,400+ active followers or passive followers of the House of Rexx Tiktok account as of April 2023. Systematic random sampling with a sample size of 80 respondents was the method used to determine the number of samples. The approach makes use of methodical data collection methods based on the study objectives, including field and library research. Descriptive analysis is the analytical technique used to resolve issues and validate theories. The results demonstrate that, in live Tiktok sessions, prospective customers of Rexx lighting goods connect with each other to a considerable and positive extent when they see visual banners.